Structural family therapy untuk memperbaiki interaksi dalam keluarga - Herliana Rahmi Saputri (Procedia : Studi Kasus dan Intervensi Psikologi, 2021)
Problems in the family is the result of a reaction to the social interaction between family members. Bad communication and obscurity of interaction between family members leads to misunderstandings in family relationships. Structural Family Therapy used to improve the pattern of communication in the family. The subject consists of three members of the family. The data were obtained using interview and observation. The intervention was carried out in ﬁve sessions. The results of the intervention were each family member has a good pattern of communication, reduced misunderstandings, clear regulations and role in the interaction between them.